Pasar Wadai Ramadhan (Cake Fair) Banjarmasin: Fading Local Food Festival - Rchwono, Yudianto; Suharto, Bambang; Isnaini, Santi (Journal of Economics and Business UBS, 2023)
This research is tended to explore the cause of declining interest in the annual food festival in Banjarmasin, Pasar Wadai Ramadhan (Ramadhan Cake Fair). This festival has been running for 38 years and only during the month of Ramadhan. It originally sells traditional delicacies and as time goes by some local spectacles are shown during the festival to attract more visitors. The aim of this research is to provide a contribution to the image strengthening of Banjaresse culture as well as economic sustainability for the people in South Kalimantan. SWOT analysis was used to conduct obtain the result of this research. The use of SWOT analysis to conduct this research is to bring out the result by conducting interviews, observation, and documentation. Based on the steps done, the result showed the cause of a lesser audience of this festival is due to the changes of occurring place for the event. To keep this annual festival sustainable, support from local authorities and locals is crucial in implementing a sustainable festival management strategy.